COSMOLOGICAL BOUNDS ON OPEN FLRW SOLUTIONS OF MASSIVE GRAVITY - Pereira, S. H. [UNESP]; Mendonca, E. L. [UNESP]; Pinho, A. S. S. [UNESP]; Jesus, J. F. [UNESP] (Univ Nacional Autonoma Mexico, Inst De Astronomia, 2016)
In this work we analysed some cosmological bounds concerning an open FLRW solution of massive gravity. The constraints from recent observational H(z) data are found and the best fit values for the cosmological parameters are in agreement with the Lambda CDM model, and also point to a nearly open spatial curvature, as expected from the model. The graviton mass dependence with the constant parameters alpha(3) and alpha(4), related to the additional lagrangians terms of the model, are also analysed, and we obtain a strong dependence on such parameters, although the condition m(g) similar or equal to H-0(-1) seems dominant for a large range of the parameters alpha(3) and alpha(4).
Keywords: cosmology: theory; dark energy; dark matter